Analysis of Surfactants by Thin-Layer Chromatography : A Review - Bhawani, Showkat Ahmad; Othman, Bin Sulaiman; Rokiah, Binti Hashim; Mohamad Nasir, Bin Mohamad Ibrahim (Carl Hanser Publisher, Munich, 2010)
Thin-layer chromatographic analysis of surfactants is presented in this review. Various chromatographic systems useful for the identification, separation and quantification of surfactants are reported. New approaches in thin-layer chromatography enable analysts to separate and determine surfactants in complex mixtures (in various environmental samples). Thin-layer chromatographic methods are mainly used for the separation of surfactants either in the separation of different classes or separation of different groups within the same class.